2015
DOI: 10.1002/cam4.551
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing of breast cancer, malignant peripheral nerve sheath tumor and neurofibroma from a patient with neurofibromatosis type 1

Abstract: Neurofibromatosis type 1 (NF1) is a genetic disorder characterized by the development of multiple neurofibromas, cafe‐au‐lait spots, and Lisch nodules. Individuals with NF1 are at increased risk of developing various tumors, such as malignant peripheral nerve sheath tumor (MPNST), pheochromocytoma, leukemia, glioma, rhabdomyosarcoma, and breast cancer. Here, we describe the exome sequencing of breast cancer, MPNST, and neurofibroma from a patient with NF1. We identified a germline mutation in the NF1 gene whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Mutations were identified in 4 genes previously implicated in MPNST pathogenesis in both human studies and genetically engineered mouse models ( NF1, TP53, EGFR , and PDGFR‐α [ PDGFRA ]) . Variants also were identified in other genes potentially involved in MPNST pathogenesis ( GNAQ, SLCO1B1, LAMA2, SLC34A2, PTCH1, RB1, KDR, CYP2A6, MYC, FLT4 , and PSMD2 ) . In addition, there were variants identified in genes not previously implicated in MPNST pathogenesis ( TYK2, CYP2D6, ABCB1, CSF1R, MAP3K1, JAK3, GNA11, FLT3, ROS1, APC, HTR2B, DPYD, ATRX, EV12A, CYP2C19, ALK, GNAS, CYP2B6, BRCA1, NOTCH1, DDR2, RAF1, SMARCB1, FLT1 , smoothened, frizzled class receptor [ SMO ], ESR1, ERBB4, CREBBBP , and ABL1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations were identified in 4 genes previously implicated in MPNST pathogenesis in both human studies and genetically engineered mouse models ( NF1, TP53, EGFR , and PDGFR‐α [ PDGFRA ]) . Variants also were identified in other genes potentially involved in MPNST pathogenesis ( GNAQ, SLCO1B1, LAMA2, SLC34A2, PTCH1, RB1, KDR, CYP2A6, MYC, FLT4 , and PSMD2 ) . In addition, there were variants identified in genes not previously implicated in MPNST pathogenesis ( TYK2, CYP2D6, ABCB1, CSF1R, MAP3K1, JAK3, GNA11, FLT3, ROS1, APC, HTR2B, DPYD, ATRX, EV12A, CYP2C19, ALK, GNAS, CYP2B6, BRCA1, NOTCH1, DDR2, RAF1, SMARCB1, FLT1 , smoothened, frizzled class receptor [ SMO ], ESR1, ERBB4, CREBBBP , and ABL1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these individuals, one 44-year-old woman previously described with the missense mutation c.2540T>C (p.Leu847Pro) had MPNST, BRCA1/2 -negative (MIM: 113705 and 600185 ) breast cancer as well as a high number of cutaneous neurofibromas (>100). 67 In addition, one individual developed a medullary thyroid carcinoma and three first-degree relatives of a Belgian proband with c.2540T>C (p.Leu847Pro) died from malignancies (a metastasized colon adenocarcinoma and two MPNSTs, both deceased before age 26). Taken together, the overall prevalence of malignant neoplasms in the studied group was substantially higher than in the published datasets of the general NF1-affected population (significant at FDR of 0.05 after B-H correction; Tables 3 and S10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that additional mutations are present in these tumors such as second hits in NF1 and TP53 , multiple copy number alterations, and deletion of CDKN2A (Ratner and Miller, 2015). Whole exome sequencing of tumors from NF1 patient with NF1 L847P revealed that each of the lesions (dermal neurofibromas, breast cancer, MPNST) harbored another mutation in NF1 ; the breast cancer and MPNST presented with additional mutations unique for each tumor (McPherson et al, 2015). …”
Section: Evidence For Functional Cooperation Of Rasopathy Genesmentioning
confidence: 99%